Uplink scheduling scheme for cloud service based on software-defined wireless network - Su PAN; Bang XIAO; Yu-qing CHEN; Sheng-mei LIU (Tongxin xuebao)
A LTE uplink scheduling scheme matching the features of wireless cloud services was proposed for the SDWN (software-defined wireless network). The scheme first solved the resource allocation problem by using the binary integer programming method, and then calculated the optimal transmission rate of cloud services in each time slot using the method of dynamic programming, finally adjusted the transmission rate of cloud services proportional to the current channel status using QoS control method in the framework of SDWN. The proposed scheme minimizes the energy con-sumption of cloud services while ensuring the transmission rate demand of multiple services. The performance of the al-gorithm is verified by simulation.